Significance of the presence of antibiotics on the microbial consortium in wastewater – The case of nitrofurantoin and furazolidone. (November 2021) - Zdarta, Agata; Smułek, Wojciech; Bielan, Zuzanna; Zdarta, Jakub; Nguyen, Luong N.; Zgoła-Grześkowiak, Agnieszka; Nghiem, Long D.; Jesionowski, Teofil; Kaczorek, Ewa
Highlights: Nitrofurantoin and furazolidone had no adverse effect on the microbial consortium. The consortium behaviour and degradation of antibiotics differed between the drugs. NFT reduced organic carbon consumption and increased EPS and VOC production. FZD decomposition exceed 60% with a small reduction of organic carbon assimilation. The consortium behaviour was better represented by the logistic mathematical model. Abstract: Antibiotics in wastewater leads to migration of pollutants and disrupts natural processes of mineralization of organic matter. In order to understand the mechanism of this, research was undertaken on the influence of nitrofurantoin (NFT) and furazolidone (FZD), on the behaviour of a consortium of microorganisms present in a model wastewater in a bioreactor. Our study confirmed biodegradation of the antibiotics by the microbial consortium, with the degradation efficiency within 10 days of 65% for FZD, but only 20% for NFT. The kinetic study proved that the presence of analysed antibiotics had no adverse effect on the microbes, but the consortium behaviour differ significantly with the NFT reducing the consumption of organic carbon in wastewater and increasing the production of extracellular biopolymeric and volatile organic compounds, and the FZD reducing assimilation of other carbon sources to a less extent, at the expense of cellular focus on biodegradation of this antibiotic.